New Product Creativity Antecedents and Consequences: Evidence from South Korea, Japan, and China. Issue 6 (10th January 2018) - Nakata, Cheryl; Rubera, Gaia; Im, Subin; Pae, Jae H.; Lee, Hyun Jung; Onzo, Naoto; Park, Heungsoo
Abstract : Creativity in new products is highly coveted by firms. However, businesses are faced with questions of how to inject creativity into new products, and whether it pays off in stronger product performance. To address these questions, a survey on key antecedents and consequences of creativity was conducted among new product managers. Based on gaps identified in the new product literature, this study examines several organizational culture (market orientation), leadership (top management involvement and risk‐taking encouragement), and national culture (secularism and survivalism) antecedents, along with new product performance consequences. Importantly, to uncover potentially complex nuances in creativity dynamics that may have been previously overlooked, the creativity construct is decomposed into novelty and meaningfulness dimensions, and the possibility of curvilinear relationships with antecedents and consequences are investigated. The study is also one of the first creativity studies based on a geography rather than a single country, specifically the cluster of South Korea, Japan, and China. In terms of antecedents, this study finds customer orientation, cross‐functional integration, top management involvement, and cultural secularism have positive linear effects on creativity's meaningfulness component, whereas top management risk taking and cultural survivalism have a negative effect. In contrast, cross‐functional integration and top management risk taking have a negative curvilinear influence on creativity's novelty component. Similar to meaningfulness, cultural secularism and survivalism have positive and negative impacts on novelty, respectively. Regarding consequences, meaningfulness has a positive linear influence on new product performance, while novelty's contribution reflects an inverted U‐shaped relationship. This finding is notable in light of previous studies that question whether novelty is helpful at all. These findings explain prior mixed results on creativity based on simple linear and aggregated effects, as well as discover new drivers and outcomes. The article concludes with theoretical and managerial implications about how firms can enhance and benefit from creativity.